MAKNA LA ILAHA ILLA ALLAH MENURUT SAID NURSI (Tinjaun dalam Perspektif Kosmologis dan Ontologi) - M. Zainuddin Alanshori; Ahmad Suyuthi (Akademika, 2019)
This research is to find out the meaning of La Ilaha Illa Allah according to Said Nursi in a cosmological and ontological perspective. This research is based on the questions on the Said Nursi's view of God and the Said Nursi's proof of the God's existence. Through a library research, it could be concluded that the meaning of la ila ha illa Allah, as explained by Said Nursi, is to explain the God's creation, the universe. Because human reason is impossible to understand God directly. therefore, there needs to be an explanation of God's creation. The explanation of God's creation is the meaning of la ilaha illa Allah according to Said Nursi. God is the Most Greatest that will not be understood by weak human reason. God is also the Most Perfect Being whose perfection cannot be compared to anything. Therefore, for Said Nursi the God's majesty and perfection are incarnated on every sheet of the face of the universe, both at the level of the macrocosm and the microcosm, through His attributes, names, and actions, which are very transparent to be witnessed by human reason.